2000
DOI: 10.1051/animres:2000134
|View full text |Cite
|
Sign up to set email alerts
|

Sources of shared variability among body shape characters at marketing age in new zealand white and egyptian rabbit breeds

Abstract: -Body measurements (body length, thigh circumference, shank length and chest width) of 311 rabbits representing three breeds, New Zealand White (NZW), Red Baladi (RB) and Black Baladi (BB) purebreds were subject to factor analysis. The objectives of this study were (a) to disclose the main sources of shared variability among body shape characters, (b) deduce the factors that describe these traits, (c) quantify the breed differences in size and shape and (d) predict live weight at marketing age from orthogonal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
15
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 14 publications
6
15
1
Order By: Relevance
“…However, the highest correlation coefficients were recorded with heart girth and thoracic circumference (0.91 and 0.84). Similar findings have been reported (Shahin & Hassan, 2000;Abdullah et al, 2003). The thigh is the area where there is the highest muscle deposition in the rabbit body (Oliveira et al) hence, its high relationship with bodyweight while the heart girth reflects gut fill.…”
Section: Resultssupporting
confidence: 90%
“…However, the highest correlation coefficients were recorded with heart girth and thoracic circumference (0.91 and 0.84). Similar findings have been reported (Shahin & Hassan, 2000;Abdullah et al, 2003). The thigh is the area where there is the highest muscle deposition in the rabbit body (Oliveira et al) hence, its high relationship with bodyweight while the heart girth reflects gut fill.…”
Section: Resultssupporting
confidence: 90%
“…The variables associated with withers height, back height and rump height had the highest loadings (component-variate correlations), followed by thoracic girth. It corroborates the submission of Pundir et al [8], Salako [10], Shahin & Hassan [11] and Yakubu & Ayoade [13], between others, for whom the PC1 can be considered as a generalized size factor. Similarly, Ruales-España & Perdomo [9] extracted eight principal components from 31 original traits and concluded that these could be of great importance in the determination of body attributes of criole Romosinuano cow.…”
Section: Discussionsupporting
confidence: 89%
“…As for males, the third axis had a high contribution of beak length, which also represented an opposite direction between beak and wattle length. The present findings are consistent with the literature, in which general size is generally reported as the main factor of variation and thus constitutive of the first axis of PCA in chickens, rabbits, or turkeys (Shahin and Hassan, 2000;Ajayi et al, 2011;Egena et al, 2014). The principal component analysis allowed for better understanding of the complex correlations among the traits and reduced the number of traits, using only the three first PCs, without loss of information.…”
Section: Principal Components Analysissupporting
confidence: 93%